PROBLEM-BASED LEARNING MODEL IN ARTS AND CULTURE SUBJECTS VOCAL ARTS MATERIALS FOR GRADE 9F AT SMPN 3 KUTOREJO - Hafizh, Doejan Grada; Suwahyono, Agus (Solah, 2025)
Abstract: This study aims to analyze the application of the problem-based learning model (PBL) in the Arts and Culture subject of vocal arts in class 9F of SMPN 3 Kutorejo. The focus of the study includes the process of implementing the model, student learning outcomes in the cognitive, affective, and psychomotor domains, and obstacles that arise during learning. The study used a descriptive qualitative approach with subjects of class 9F students and Arts and Culture teachers, and the object was the process of learning vocal arts through PBL. Data were obtained through observation, interviews, documentation, and literature studies, then analyzed using reduction, presentation, and conclusion drawing techniques, and tested through triangulation of sources and techniques. The results showed that the application of PBL increased students' activeness, creativity, and understanding of vocal techniques, especially in aspects of breathing, articulation, and expression. Students actively participated in finding and solving vocal problems through group exercises and performances. Improvements were seen in cognitive abilities, attitudes of responsibility and cooperation, and vocal skills. Obstacles found included lack of interest, self-confidence, and mastery of basic techniques. Teachers addressed these through out-of-class learning and intensive guidance. Overall, this model effectively improved students' competence and character in learning vocal arts.